2020
DOI: 10.3389/fendo.2020.00412
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Weight Management: A Review of the Latest Evidence to Inform Practice

Abstract: Over the last decade, mobile technology has emerged as a potentially useful platform to facilitate weight management and tackle the current obesity epidemic. Clinicians are being more frequently asked to give advice about the usefulness of mobile apps and many individuals have already integrated apps into their attempts to manage weight. Hence, it is imperative for clinicians involved in weight management to be aware of the latest developments and knowledge about available mobile apps and their usefulness in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 73 publications
1
59
0
3
Order By: Relevance
“…The authors concluded that the inclusion of additional strategies could make apps more helpful to users who have motivational challenges. On the other hand, systemic reviews and metanalysis [ 9 , 41 , 42 ] performed in past years revealed that dietary interventions including self-monitoring based on nutrition-related apps may be a useful tool for weight management or reduction. Flores Mateo, et al [ 9 ] analyzed 12 articles and observed that the use of a mobile app was associated with significant changes in body weight (kg) and body mass index (kg/m 2 ), −1.04 kg and −0.43 kg/m 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the inclusion of additional strategies could make apps more helpful to users who have motivational challenges. On the other hand, systemic reviews and metanalysis [ 9 , 41 , 42 ] performed in past years revealed that dietary interventions including self-monitoring based on nutrition-related apps may be a useful tool for weight management or reduction. Flores Mateo, et al [ 9 ] analyzed 12 articles and observed that the use of a mobile app was associated with significant changes in body weight (kg) and body mass index (kg/m 2 ), −1.04 kg and −0.43 kg/m 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Latest obesity management guidelines advocate for the implementation of emerging technologies and virtual medicine incorporating online education, coaching as well as weight and activity tracking to improve weightloss outcomes [14]. Although numerous applications are available for weight loss and diabetes management and mobile health interventions hold great promise to optimize treatment strategies for several chronic diseases, many studies using such applications (apps) are of insufficient quality [15,16]. There is also room for improvement as the functionality of some apps is limited and app development is rarely evidence-based [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to a literature review related to the prevention and management of MetS, about a third of the studies were only targeting the middle-aged population, and over 60% were concerned about people already living with MetS. On the other hand, studies on young adults, a group with the highest success rate of MetS prevention, were scarce [ 25 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%